2019
DOI: 10.1111/jocd.13102
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of plantar warts using topical Zijinding, a traditional Chinese medicine preparation: A case series

Abstract: Introduction Plantar warts are associated with high transmissibility and morbidity. Among the available therapeutic options, none is uniformly effective or virucidal. Salicylic acid is the first‐line therapy but approximately one‐third of lesions could not resolve and become recalcitrant despite repeated treatment. Cryotherapy is widely accessible with low cost but may be complicated by pain, blister formation, hemorrhage, infection, excessive granulation tissue formation, and hyper‐/hypo‐pigmentation. Hence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Evidence has suggested that some herbal medicines and TCM prescriptions exhibit remarkable antiviral bioactivity [ [9] , [10] , [11] ]. However, whether they can be used exclusively for the treatment of PWs in clinical practice remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has suggested that some herbal medicines and TCM prescriptions exhibit remarkable antiviral bioactivity [ [9] , [10] , [11] ]. However, whether they can be used exclusively for the treatment of PWs in clinical practice remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the antiproliferative effects of arsenic on cancer cells are caused by a combination of several factors, such as modulation of intratumoral mitochondrial integrity [ 22 , 30 ] and inflammatory response [ 31 ], reactive oxygen species generation [ 32 ], and the induction of pro-apoptotic genes and suppression of cell death resistance mechanisms [ 33 ]. Regarding skin lesions treatment, there is evidence both in vitro and in vivo that supports the use of arsenic compounds in psoriasis [ 34 ], plantar warts [ 35 ], and melanoma [ 36 ]. These findings portray AsNPs as a promising agent to be used as adjuvant therapy against other types of tumors where standard chemotherapy has limited success rates.…”
Section: Introductionmentioning
confidence: 99%